Módulo electromecánico para balanceo de cargas en líneas trifásicas mediante una red de sensores (2018)
This document describes the process of design and assembly of a system that combines an electronic circuit with electromechanical relays to switch the connection between the 3 phases that feed 3 single-phase load circuits with resistors in parallel. The module was designed as a system with 3 stages: control, switching and current sensors. A fourth communication stage can be inferred from the fact that the module can be connected both by USB protocol and BLUETOOTH. This work also reports the first advance in the development of the project DESIGN OF AN ANDROID APPLICATION FOR THE MONITORING AND REMOTE CONTROL OF AN INTEGRATED SENSOR NETWORK, which main objective is to implement a program at the mobile application level to facilitate the balance of charges in three-phase networks through remote monitoring.